Communication assessment of the bilingual, bicultural child : issues and guidelines - Erickson, Joan Good; Omark, Donald R. (Baltimore, MD : University Park Press, 1981)
Hoe verloopt de integratie via taal bij kinderen die leven in twee culturen en twee talen spreken?
Bibliography: p. 297-358.
Includes index.
Keywords: Education, Bilingual -- United States; Language arts -- Ability testing; Bilingualism -- United States; Biculturalism -- United States